Brake System and its Control Strategy of Autonomous-rail Rapid Tram - QIAN Hua; YU Jieren; LUO Xiaofeng; FU Jianchao; LIU Wenfeng; XIE Yongqing (Kongzhi Yu Xinxi Jishu)
Based on the particularity of rail and road applications, this paper analyzed the special requirements of brake system for autonomous-rail rapid tram. Also, the top design goals and the overall scheme design were mentioned. Finally, the dynamic test results show that this new brake system can satisfy the safety requirements of passenger and road while ensuring the comfort requirement of passenger onboard.